2004
DOI: 10.1016/j.pain.2004.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal opioid treatment for chronic non-malignant pain: a 3-year prospective study

Abstract: Intrathecal (IT) opioid therapy is a treatment alternative for patients with severe chronic non-malignant pain. Several uncontrolled retrospective and prospective outcome studies have suggested a benefit in chronic non-malignant pain patients, but uncertainties about patient selection in these studies weaken the results. This study evaluated long-term outcome of IT opioid therapy in chronic non-malignant pain prospectively, and included two comparative groups to improve understanding of selection criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 10 publications
8
68
0
1
Order By: Relevance
“…On a population basis, the relationship between alcohol intake and coronary mortality is a U or J shape. A recent long-term study of [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] year olds showed that the 6% who took up moderate alcohol were 38% less likely to develop CAD compared to their persistently nondrinking counterparts [34]. The consistent association between moderate alcohol intake (2 units a day for women and 3 units a day for men) and cardiovascular risk reduction is attributed to beneficial effects on HDL-cholesterol, fibrinogen and glucose intolerance [35].…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…On a population basis, the relationship between alcohol intake and coronary mortality is a U or J shape. A recent long-term study of [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] year olds showed that the 6% who took up moderate alcohol were 38% less likely to develop CAD compared to their persistently nondrinking counterparts [34]. The consistent association between moderate alcohol intake (2 units a day for women and 3 units a day for men) and cardiovascular risk reduction is attributed to beneficial effects on HDL-cholesterol, fibrinogen and glucose intolerance [35].…”
Section: Dietmentioning
confidence: 99%
“…Long-term outcomes are uncertain. A prospective case study followed 38 intrathecal pump recipients for 3 years after implantation and concluded that although intrathecal analgesic administration may improve pain, mood and function, this group of patients continue to experience severe symptoms [47]. Importantly, there is little evidence of overall benefit to chronic angina patients using intrathecal infusion pumps and worldwide experience is limited to a very small number of specialist units [48].…”
Section: Opioid Drugsmentioning
confidence: 99%
“…Et pourtant, ces techniques qui sont loin d'être récentes, font l'objet de très nombreuses publications et études scientifiques [16] dont les toutes dernières adoptent une méthodologie scientifique rigoureuse, reposent pour certaines séries sur des centaines de malades [23], bref tout est réuni pour pouvoir dégager une position et essayer autant que faire se peut, de se déconnecter de cette position de l'affectif qui encore une fois caractérise souvent le regard que nous portons sur ces techniques.…”
Section: Introductionunclassified
“…The benefits of IDT are manifested in improved pain control, functional capability, health-related quality of life, while containing the demand for health care resources. [6][7][8][9][10][11][12][13] IDT is a minimally invasive therapeutic technique that relies on implantation of a variety of drug delivery systems, with accessories using either programmable or nonprogrammable pumps. The system enables administration of analgesics directly into the intrathecal space.…”
mentioning
confidence: 99%